Agricultural waste management practices in Trishal upazilla, Mymensingh - Akhter, Tangina; Ashraf, Md Ali; Hassan, Md Monirul; Akhter, Farzana; Riza, Azmira Nasrin (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to assess the present status of agricultural waste management by farmers in Trishal upazila of Mymensingh district, Bangladesh. During April to May 2015 and data were collected from the sample of 70 farmers and 5 farms. A structured interview schedule was used for collection of data. The study explored the relationship between the four selected type farming (independent variable) of farmers with their generation of agricultural waste (dependent variable). In this study the highest amount waste (straw and husk production) is closely related with the size of cropland. Straw production less than or equal 1000 kg is 36.62%, straw production less than or equal 10000 kg is 54.92%, straw production less than or equal 20000 kg is 5.63% and straw production less than or equal 30000 is 2.81% and husk production less than or equal 1000 kg is 35.71%, husk production less than or equal 10000 kg is 55.71%, husk production less than or equal 15000 kg is 8.57%. So as the dairy and poultry waste is also relate with the number of cows and birds. Average amount of dung is 8.87 kg per day and average amount of used litter was 46.36 kg per 800 bird production. For management biogas was suggested by 12.5 percent respondent. Composting and fish culture were suggested individually by 4.17 and 8.3 percent respectively. Due to manage agricultural waste efficiently it is necessary to initiating program to introduce the economic benefits of waste management and start training programs for farmers. Res. Agric., Livest. Fish.3(3): 395-402, December 2016